LEGAL CHARACTERISTICS OF THE SUBJECT AND THE SUBJECTIVE SIDE OF THE CRIME – PILGGER - Piskun, Ivan; Ustych, Oleksandr (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of the article is aimed at researching the concept and signs of the composition of the legal characteristics of the subject and the subjective side of the crime of looting, as well as conducting a systematic analysis of the features of the legal composition of this criminal offense. Research methods are the main methods and means of knowledge, such as: documentary analysis and synthesis, comparison, objective truth, cognitive-analytical, interdisciplinary method of legal research, generalization. Results: the concepts and features of the legal composition of the crime of looting were comprehensively studied. The current state of Ukrainian legislation regarding the criminal offense of looting is analyzed. Also, taking into account the conducted research and study of scientific legal literature, which reveals the essence and content of each of the elements of the criminal offense, and looting itself, it was established that the subjects of looting are military personnel, conscripts, reservists during their training (they can be both citizens of Ukraine and foreigners, stateless persons, fit for military service due to their health). The definition of the subjects of such a criminal offense as looting allows to consider the subjective side of looting as the fault of direct intent (to qualify the illegal actions of the subject of looting, there must necessarily be a selfish motive, i.e. taking possession of the victim’s belongings for the purpose of one’s own material gain). Discussion: the subject and the subjective side of looting are mandatory parts of the legal composition of this crime, without which it is invalid. At the same time, looting is considered completed from the moment when the offender is able to dispose of the stolen items at his own discretion.